Principal Academic Supervision: Performance, Problems and Solutions - Yari Dwikurnaningsih; Reinhard Leonardo Paais (Jurnal Pendidikan Indonesia, 2022)
Supervision is an important activity that must be carried out by every educational institution to realize a quality education through coaching, repairing and increasing the professionalism of teachers and school staff. This quality education is closely related to school efforts in producing quality human resources. This research was conducted with the aims to analyses the performance of the principal’s academic supervision. This study use qualitative method. This study implementation problems and solutions with 4 principals and 8 teachers as the subject. Data collection techniques using interviews, document studies and observation. The data was validated using technical triangulation and source triangulation. The collected data is then analyzed using the Miles and Huberman model stages, were: data collection, data reduction, data display and drawing conclusions. The results showed that the average score of the principal’s performance at the planning stage of academic supervision was 25% (less category), the implementation stage of academic supervision was 46,8% (less category) and the follow-up stage of academic supervision was 30% (less category). Various problems are also found in the implementation of academic supervision so that the supervision model with a collaborative approach can be the right solution to be applied.